O Cost/effectiveness of dressings for chronic wounds in Primary Care. (REMUNOM, 2025)
Chronic wounds are persistent skin lesions resulting from the decompensation or discontinuity of the epithelial tissue, resulting from trauma, surgeries, or chronic diseases. The objective of the study was to analyze the cost of dressings in chronic wounds compared to the use of materials with greater scientific evidence. This is a case study conducted from an interview with a user of the UBS with a chronic wound for 20 years and an analysis of medical records. Expenditures of approximately R$80,901.60 were identified, considering only the cost of the material, without accounting for labor costs, transportation, and quality of life. If more resolutive material were used, the approximate cost per week would be R$31,93. It was concluded that the use of dressings with higher scientific evidence could provide a better cost/benefit, as the healing time becomes more effective, even though the cost of the material is higher for initial investment.